Distinctive Roles of Sirtuins on Diabetes, Protective or Detrimental? - Song, Jie; Yang, Bing; Jia, Xiaobin; Li, Mingyu; Tan, Wei; Ma, Shitang; Shi, Xinhong; Feng, Liang (Frontiers in Endocrinology, 2018)
Dysregulation of metabolic pathways leads to type 2 diabetes, characteristic of high glucose concentration caused by insulin resistance. The histone deacetylases sirtuins exhibit remarkable enzymatic activities. Accumulating evidence indicates that sirtuins can be pharmacologically activated to ameliorate diabetes. Here, we evaluated different roles of sirtuins (SIRT1-SIRT7) in diabetes progression and described their involvement in metabolic pathways of skeletal muscle, adipose tissue and liver. The nuclear sirtuins, SIRT1, SIRT6 and SIRT7, regulate the activity of key transcription factors and cofactors in almost all tissues with the cellular responses to energy demands. The mitochondrial sirtuins, SIRT3, SIRT4 and SIRT5, regulate the activity of mitochondrial enzymes in response to fasting and calorie restriction. Moreover, genetic polymorphisms of SIRT1 and SIRT2 have been reported to associate with diabetes development. It's worth noting that SIRT1, SIRT2, SIRT3, and SIRT6 are positive regulators of insulin resistance in most cases. In the opposite, SIRT4 and SIRT7 inhibit insulin secretion and fatty acid oxidation. Identification of SIRT1 activators for diabetes has gained wide attention, such as metformin, resveratrol, and resveratrol derivatives. Randomized, prospective, and large-scale clinical trials are warrant to uncover the responsibilities of SIRTs modulators on diabetes progress.